Pemanfaatan Software Bone dalam Pembuatan Sistem Kasir pada Percetakan Kingprinting - Febrianto, Muhammad Dika; Wartariyus, Wartariyus (Jurnal Ilmu Siber dan Teknologi Digital, 2023)
Purpose: In this era of technology has a very important role in the progress of society, we are forced to adapt to an era that has fast-paced information, this is because the development of information technology can provide fast and accurate information and can even affect several businesses, one of which is the printing industry business even in the printing industry alone. Methodology: The financial information department has a very important role, on the other side of the job manuals that have a relationship with numbers sometimes have a big risk of miscalculation from employees (Human Error) by utilizing bone software for cashier systems which are expected to help printing companies to manage financial transactions and goods transactions related to printing. Results: This research has succeeded in utilizing the Bone software in the transaction of goods and buying and selling. The conclusion of this study is the use of bone software in manufacturing the cashier system was successfully built according to the agreed changes, proven by the test results as being as expected.